Implementasi Kebijakan E-Government Melalui Website Subang.go.id Di Dinas Komunikasi dan Informatika Kabupaten Subang - Regan Vaughan; R. Hari Busthomi; Anggi Andani Putri (Ridwan Institute, 2021)
Technological developments require every aspect of life to adapt to the digital era, as well as the world of government. The birth of this digital era indeed provides solutions or strategies that have a very significant impact on improving the performance of public services that can support the creation of good governance. The challenges of the digital era in the midst of bureaucracy encourage expectations of openness, speed and accuracy of public services provided by the government. The Subang Regency Government innovates public services which are often known as E-Government, one of the uses of E-Government through the subang.go.id website. The purpose of this research is to get an overview of the implementation of e-government policies through the subang.go.id website as well as the obstacles as well as the efforts made to overcome these obstacles. The research method used in this research is descriptive research method with a qualitative approach. Data collection techniques used in the form of observation, interviews, and documentation. The informants in this study were two people consisting of the Head of E-Government Services and the Head of Application Development. The results of this study indicate that the implementation of the E-Government Policy through the subang.go.id website is considered good. Based on the evaluation results of the Kemenpan-RB Subang Regency is already in the Good predicate with an Index Value of 3.01. It's just that in the implementation of E-Government through the website there are still things that need to be improved regarding the consistency or discipline of all parties and the addition of competent management staff. The conclusion from the results of this study in terms of the implementation of E-Government Policy through the subang.go.id website at the Communication and Information Office of Subang Regency is considered good.